Clostridium acetobutylicum atpG-Knockdown Mutants Increase Extracellular pH in Batch Cultures - Jang, Yu-Sin; Seong, Hyeon Jeong; Kwon, Seong Woo; Lee, Yong-Suk; Im, Jung Ae; Lee, Haeng Lim; Yoon, Ye Rin; Lee, Sang Yup (Frontiers in Bioengineering and Biotechnology, 2021)
ATPase, a key enzyme involved in energy metabolism, has not yet been well studied in Clostridium acetobutylicum. Here, we knocked down the atpG gene encoding the ATPase gamma subunit in C. acetobutylicum ATCC 824 using a mobile group II intron system and analyzed the physiological characteristics of the atpG gene knockdown mutant, 824-2866KD. Properties investigated included cell growth, glucose consumption, production of major metabolites, and extracellular pH. Interestingly, in 2-L batch fermentations, 824-2866KD showed no significant difference in metabolite biosynthesis or cell growth compared with the parent ATCC 824. However, the pH value in 824-2866KD cultures at the late stage of the solventogenic phase was abnormally high (pH 6.12), compared with that obtained routinely in the culture of ATCC 824 (pH 5.74). This phenomenon was also observed in batch cultures of another C. acetobutylicum, BEKW-2866KD, an atpG-knockdown and pta-buk double-knockout mutant. The findings reported in this study suggested that ATPase is relatively minor than acid-forming pathway in ATP metabolism in C. acetobutylicum.